A Linguistic Look at lalei͂n glṓssē - Benware, Wilbur A. (The Bible translator, 2025)
The expression lalei͂n glṓssē/glṓssais has been at the center of controversies in interpretations of 1 Cor 12–14, Acts 2, 10, 19, and in the longer ending of Mark. Its syntax and meaning are examined here both synchronically and diachronically to determine its origin and its meaning. Grammatically, the expression is odd, since glṓssē is redundant, being inherent in the semantics of the verb. Its explicit appearance is thus unusual and raises the question as to the reason for its appearance, i.e., what the coinage intended to convey. In Corinth, lalei͂n glṓssē referred to the ecstatic speech called glossolalia. When Paul’s letter was read in other churches where glossolalia was unknown, the expression was reinterpreted as speaking a foreign language, either miraculously (xenoglossia) or naturally. The latter view persisted in the following centuries in the church fathers.